CHARACTERS OF PERSONAL TEMPERAMENT IN SPEECH EXPRESSION (World Bulletin of Social Sciences, 2023)
The article talks about the influence of personality traits, in particular, temperament, on text structure. It describes linguocholeric, linguosanguinic, linguophlegmatic, and linguomelancholic types
Keywords: speech; personality traits; temperament; linguocholeric